Evaluation of Antiepileptic Activity of Flowers of Cocos nucifera L. Against Experimentally Induced Convulsions in Rats - B, Archana; Mudavath, Ravi Naik; Enumula, Vinay; Ravali, N; Sravan Kumar, Paka (Journal of Drug Delivery and Therapeutics, 2021)
The report used to be planned to analyze the antiepileptic activity of Cocos nucifera flowers against special experimentally induced convulsions in rats. In the present study, antiepileptic activity was assessed by following experimental models. Anti-convulsant in vivo models: Maximal electroshocks (MES) induced models in rats, Pentylenetetrazole (PTZ) induced in rats. Pretreatment of animals with Cocos nucifera flowers extract has reduced by half the general continuance of tonic hind leg extension, the most commonly used endpoint in assessing clonic convulsions. MES provokes repetitive neuronal firing indicates epileptic neurons. MES is the widely accepted model to demonstrate the antiepileptic property of a drug. This property is antagonistic of the plant extract could flow from to blockade of voltage-gated sodium channel or due to effect on NMDA receptors. The Cocos nucifera flowers extract was also demonstrated potential anticonvulsant activity in PTZ induced convulsions and this may be due to its agonistic activity on the GABAA receptor. This is further supported by an elevated level of GABA by the plant extract in the PTZ model. Methanolic extract of Cocos nucifera flowers has shown significant anticonvulsant activity against MES and Pentlylenetetrazole induced convulsion models. This observed activity could also be the referable presence of flavonoids and other phytochemical constituents found in the powerful extract.Keywords: Cocos nucifera, antiepileptic activity, Maximal electroshock, Pentlylenetetrazole, Flavonoids,